Short anagen syndrome of the hairline in 3 generations. - Milano, A. (European Journal of Pediatric Dermatology, 2020)
Short anagen syndrome should be suspected when the history speaks of hair that has never grown beyond a certain length and has never been cut. Twenty cases of short anagen syndrome have been described in the relevant literature, all in females except one case in a male subject (10). The diagnosis is confirmed by physical examination, which shows uniformly and abnormally short hair in the absence of fragility, structural alterations or inflammatory phenomena of the scalp, and by microscopic examination, which shows a significant reduction of the hair in anagen and the presence of tapered tips, confirming the claim that they were never cut. […]